Design, synthesis, and functional evaluation of CO‐releasing molecules triggered by penicillin G amidase as a model protease - Sitnikov, Nikolay S.; Li, Yingchun; Zhang, Danfeng; Yard, Benito A. (Angewandte Chemie. International edition, 2015)
Abstract Protease?triggered CO?releasing molecules (CORMs) were developed. The viability of the approach was demonstrated through the synthesis of compounds consisting of an ?4?oxydiene?Fe(CO)3 moiety connected to a penicillin?G amidase (PGA)?cleavable unit through a self?immolative linker. The rate of PGA?induced hydrolysis was investigated by HPLC analysis and the subsequent CO release was quantitatively assessed through headspace gas chromatography. In an in?vitro assay with human endothelial cells, typical biological effects of CO, that is, inhibition of the inflammatory response and the induction of heme oxygenase?1 expression, were observed only upon co?administration of the CORM and PGA. This work forms a promising basis for the future development of protease?specific CORMs for potential medicinal applications.
Gesehen am 22.03.2018